A hydrogen fuelled LH2 tanker ship design - Alkhaledi, Abdullah N. F. N. R.; Sampath, Suresh; Pilidis, Pericles (Taylor and Francis, 2021)
This study provides a detailed philosophical view and evaluation of a viable design for a large liquid hydrogen tanker fuelled by liquid hydrogen. Established methods for determining tank sizing, ship stability, and ship characteristics were used to evaluate the preliminary design and performance of the liquefied hydrogen tanker named ‘JAMILA’, designed specifically to transport liquid hydrogen. JAMILA is designed around four large liquid hydrogen tanks with a total capacity of ∼280,000 m3 and uses the boil-off gas for propulsion for the loaded leg of the journey. The ship is 370 m long, 75 m wide, and draws 10.012 m at full load. It has a fully loaded displacement tonnage of 232,000 tonnes to carry 20,000 tonnes of hydrogen. Its propulsion system contains a combined-cycle gas turbine of approximately 50 MW. The volume of the hydrogen cargo pressurised to 0.5 MPa primarily determines the size and displacement of the ship.
Keywords: liquefied Hydrogen; LH2 tanker; ship design; liquid hydrogen tank